Peran Perpustakaan Sekolah dalam Mendukung Kegiatan Olimpiade Sains Nasional (OSN) di SMA Muhammadiyah Wonosobo - Vany Rahmawaty; Ika Krismayani (Prodi S1 Ilmu Perpustakaan dan Informasi, Fakultas Ilmu Budaya, Universitas Diponegoro, 2023)
[The Role of the School Library in Supporting Olimpiade Sains Nasional (OSN) Activities at SMA Muhammadiyah Wonosobo] Olimpiade Sains Nasional (OSN) is one of the branches of competition that contributes many achievements for a school. Not only the ability of students is a factor in the success of OSN, but there are other factors such as the presence of teachers who become OSN mentors, the availability of school facilities, and the learning atmosphere. One of the school facilities that support OSN success is the school library. This research discusses the role of the library of SMA Muhammadiyah Wonosobo in supporting the activities of the Olimpiade Sains Nasional (OSN). The research method used is qualitative research with a phenomenological approach. Data collection methods in this study were observation, semi-structured interviews, and documentation studies. The results showed that SMA Muhammadiyah Wonosobo Library has a role in supporting OSN activities. The support is in the form of providing library facilities and collaboration that the library does with various parties. However, the library still has various obstacles such as collections that have not been updated, the classification process, and funding.